PENGARUH KUALITAS PRODUK DAN SOCIAL MEDIA MARKETING TERHADAP PURCHASE INTENTION KONSUMEN PADA PRODUK KOSMETIK SOMETHINC DI KOTA SALATIGA - Dita Ayu Fitriana; Saryadi Saryadi; Dinalestari Purbawati (Jurnal Ilmu Administrasi Bisnis, 2024)
Many beauty products are offered, such as "Somethinc", a cosmetic brand from PT. Royal Pesona Indonesia which was established in 2019. According to Somethinc’s sales ranking data from several stores in Salatiga reveals fluctuating and comparatively lower sales figures when compared to rival brands. Negative comments, consumer confusion about their products, and delayed or no responses from Somethinc can potentially reduce consumer interest. This research was conducted to determine the influence of product quality and social media marketing on consumer purchasing intentions of Somethinc products in Salatiga, used 100 sample of respondents (people in Salatiga who are social media users who are interested in and/or have bought or used Somethinc). This research is quantitative research with survey methods (questionnaires). The data analysis used SPSS 25. The results show that there is a positive and significant influence between product quality and social media marketing on consumer purchasing intentions of Somethinc cosmetic products. Product quality affects 46.9% and social media marketing affects 54.3%. Simultaneously, these two variables affect purchase intention by 78.8%. Based on these results, Somethinc needs to re-evaluate its products, especially if there are many negative comments. Furthermore, Somethinc also should intensify sharing its content to attract more consumers.Keywords: Product Quality; Purchase Intention; Social Media MarketingBeragam produk kecantikan ditawarkan, salah satunya “Somethinc”, brand kosmetik yang didirikan tahun 2019 oleh PT Royal Pesona Indonesia. Berdasarkan data rangking penjualan Somethinc beberapa store di Kota Salatiga, diketahui penjualan Somethinc fluktuatif dan cenderung rendah dibandingkan pesaing. Dijumpai komentar negatif, kebingungan konsumen terkait produk, serta keterlambatan/ketiadaan respon dimana ini berpotensi mengurangi minat konsumen. Penelitian ini dilakukan untuk mengetahui pengaruh kualitas produk dan social media marketing terhadap purchase intention konsumen Somethinc di Kota Salatiga. Penelitian ini merupakan penelitian kuantitatif dengan metode survei (kuesioner), dengan sampel sebanyak 100 orang dari responden (masyarakat Kota Salatiga dan merupakan pengguna medsos yang tertarik dan/atau pernah membeli/menggunakan Somethinc). Analisis data penelitian menggunakan SPSS versi 25. Hasil dari penelitian menunjukkan bahwa terdapat pengaruh positif dan signifikan antara kualitas produk dan social media marketing terhadap purchase intention. Kualitas produk berpengaruh sebesar 46,9% dan social media marketing sebesar 54,3%. Secara simultan, keduanya berpengaruh sebesar 78,8%. Berdasarkan hasil tersebut, Somethinc perlu mengevaluasi kembali produknya. Diharapkan pula Somethinc dapat meningkatkan gebrakan social media marketing-nya, misalnya dengan meningkatkan intensitas membagikan konten supaya dapat menarik konsumen lebih banyak.Kata Kunci: Kualitas Produk; Purchase Intention; Social Media Marketing